Kaidah yang berkaitan dengan zhihar - Wahda Hilwani Damanik (P2WP MUI Sumatera Utara, 2024)
The fiqh principle of ?????? (Zhihar) is one of the important concepts in Islamic family law that regulates the interaction between husband and wife, especially related to the issue of divorce. Zhihar comes from the tradition of jahiliyah, where a husband utters words that equate his wife with a mahram's body part that is forbidden to marry, such as a mother or a biological sister, thus forbidding the husband-wife relationship. In the context of Islamic law, zhihar is not divorce, but it requires the husband to pay kafarat (ransom) so that the husband-wife relationship can be halal again. The required kafarat is in the form of freeing slaves, fasting for two consecutive months, or feeding 60 poor people. However, there are several exceptions in the application of the zhihar principle, especially related to the intention, seriousness, and psychological condition of the husband. This study aims to analyze the zhihar principle from the perspective of Islamic law. This study uses a qualitative approach with a literature study method, analyzing fiqh texts from various schools of thought and interpretations to understand the concept and implications of the law of zhihar. Zhihar is considered a major sin in Islam and does not invalidate a marriage. Husbands who perform zhihar are obliged to pay kafarat. If the husband dies before paying the kafarat, the kafarat obligation is no longer valid. However, the wife is still entitled to maintenance and other rights during the iddah period.